2012
DOI: 10.1038/mp.2012.10
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional astrocytic regulation of glutamate transmission in a rat model of depression

Abstract: Depression is usually associated with alterations in the monoaminergic system. However, new evidences suggest the involvement of the glutamatergic system in the aetiology of depression. Here we explored the glutamatergic system in a rat model of depression (i.e., the flinders sensitive line (FSL)) to reveal the mechanism underlying the emotional and cognitive aspects associated with the disease. We showed a dramatically elevated level of baseline glutamatergic synaptic transmission by whole-cell recordings as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 50 publications
8
95
0
1
Order By: Relevance
“…First, increased baseline glutamatergic transmission may be a player in the pathophysiology of depression. This proposal is supported by a recent study that uncovered enhanced basal glutamatergic transmission in a rat model of depression (40). Moreover, several studies support the involvement of increased glutamate release in the context of depression and stress-related behaviors (41).…”
Section: A Synaptic Mechanism For Ketamine Actionmentioning
confidence: 82%
“…First, increased baseline glutamatergic transmission may be a player in the pathophysiology of depression. This proposal is supported by a recent study that uncovered enhanced basal glutamatergic transmission in a rat model of depression (40). Moreover, several studies support the involvement of increased glutamate release in the context of depression and stress-related behaviors (41).…”
Section: A Synaptic Mechanism For Ketamine Actionmentioning
confidence: 82%
“…The distribution and the expression levels of GLAST and GLT-1 have been studied widely in brain injury and other neurological disorders (Mitosek-Szewczyk et al, 2008;Rao et al, 1998). Additionally, emerging studies have explored the glutamatergic system in a depression model and revealed the mechanism underlying the emotional and cognitive factors associated with depression (Gomez-Galan et al, 2013;Zhu et al, 2014). Evidence has emphasized that the dysfunction of astrocytic glutamate regulation, including the down-regulation of the glial glutamate transporter GLAST, is involved in both synaptic plasticity and memory impairments (Gomez-Galan et al, 2013;Potier et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, emerging studies have explored the glutamatergic system in a depression model and revealed the mechanism underlying the emotional and cognitive factors associated with depression (Gomez-Galan et al, 2013;Zhu et al, 2014). Evidence has emphasized that the dysfunction of astrocytic glutamate regulation, including the down-regulation of the glial glutamate transporter GLAST, is involved in both synaptic plasticity and memory impairments (Gomez-Galan et al, 2013;Potier et al, 2010). In Parkinson's disease, studies have demonstrated an association between disrupted glutamatergic neurotransmission and glutamate transporter functioning; however, to our knowledge, the relationship between glutamate transporters and PTSD is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, a reduction in astroctyte number most consistently correlated with regions with reduces volumes [77]. Later in stress-based rodent models, pervasive astrocytic deficits were widely reported including cell loss [7881] and decreased glutamate uptake from the synaptic cleft [8284]. Apart from their extensively characterized roles in demyelinating disorders, such as multiple sclerosis and leukodystrophies, OL-lineage cells have been heavily implicated in schizophrenia.…”
Section: Association Of Ng2-glia With Neuropsychiatric Disordersmentioning
confidence: 99%